PENGARUH PERBENDAAN KOMPOSISI TEPUNG TAPIOKA TERHADAP KUALITAS BAKSO LELE - Zulkarnain, Juita; Yusuf, Liswarti; yuliana, yuliana (Journal of Home Economics and Tourism, 2013)
AbstractThis research aimed to analyze the different affect of tapioca’s composition which 15%, 25%, 35% to the quality of shape, colour, flavor, texture and the taste ofcatfish bakso. The kind of this research is experimental using complete randomdesign with 1 factor which is the amount of tapioca’s with difference the composition(15%, 25%, 35%) with 4 times repeat, that did in the Tata Boga Jurusan KK FT UNPworkshop in December 2012. The hypothesis shows that there is an affect of the usedof tapioca’s 15%, 25% and 35% to the catfish bakso quality. Tapioca’s compositionshows that the us of 15% tapioca’s give the better affect to the flavor, savory, and leletaste dominantly. For the 25% tapioca’s give the better affect to all indicators. Andfor the 35% tapioca’s give the better affect to the colour, chewy texture, smooth fibertexture and for the hedonic test shows that bakso with 25% tapioca’s is mostlyfavored.Keywords : bakso, catfish, tapioca